The experience of using e-commerce platforms affects the online purchase intention of customers in the FMCG (Fast moving consumer goods) sector in Hanoi city - Pham Van Tuan, PhD; Nguyen Minh Ha; Bui Duy Hiep; Nguyen Quang Huy; Tran Thi Ngoc Mai; Pham Mai Phuong (The Institute of Academic Research and Publication (IARP), 2022)
In recent times, the Vietnamese e-commerce market is in a period of strong development, in addition, to the sharp increase in people’s demands to join e-commerce platforms after the epidemic. The research group started with an overview study, then research hypotheses and models were proposed. After conducting preliminary qualitative and quantitative research to adjust the appropriate scales, the research group created a questionnaire and collected data in online forms with a sample size of 350. Next, the data was entered into the software for SEM analysis. The results of the study indicate that the quality of the e-commerce platform has an indirect impact on the purchase intention through the positive impact on the trust and the negative impact on the perceived risk. Attitudes towards information, trust, perceived risk, and perceived usefulness have direct influences on purchase intention. Attitude towards information, trust, and perceived usefulness have positive effects on purchase intention, while perceived risk harms purchase intention. In addition, purchase intention is relatively strongly influenced by trust and perceived usefulness. Perceived risk and attitude towards information have little influence on purchase intention. Finally, the research team proposes some solutions for businesses to increase the purchase intention of consumers through e-commerce platforms.